Evaluation of radio broadcasts on livestock feed and forage technologies - Mesfin, Hailemariam; Mekonnen, Kindu; Bezabih, Melkamu; Adie, Aberra; Gebreyes, Million; Assefa, Getnet; Seifu, Haimanot (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The International Livestock Research Institute (ILRI) works for better lives through livestock in developing countries. ILRI is co-hosted by Kenya and Ethiopia and has 14 offices across Asia and Africa. The institute is one of the CGIAR research centres, a global research partnership for a food-secure future. CGIAR science is dedicated to reducing poverty, enhancing food and nutrition security, and improving natural resources and ecosystem services. Its research is carried out by 15 CGIAR centres in close collaboration with hundreds of partners, including national and regional research institutes, civil society organizations, academia, development organizations and the private sector. Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) is a program funded by the United States Agency for International Development (USAID) and operates in six African countries (Mali, Ghana, Tanzania, Malawi, Zambia and Ethiopia). The program aims to contribute to Feed the Future goals of reducing hunger, poverty and under-nutrition by delivering high quality research outputs that are relevant to these goals. Through action research and development partnerships, Africa RISING is creating opportunities for smallholder farm households to move out of hunger and poverty through sustainably intensified farming systems that improve food, nutrition and income security, particularly for women and children, and conserve or enhance the natural resource base. In Ethiopia, the main aim of the project is to identify and validate solutions to the problems experienced by smallholder crop–livestock farmers. Some problems arise from the difficulties facing farmers in managing natural resources and achieving efficiencies from managing crops, trees, water and livestock together. These efficiencies are often influenced by other factors such as access to inputs and reliability of markets. To address this complexity, Africa RISING takes an integrated approach to strengthening farming systems. It conducts participatory research that identifies technologies and management practices that work for farmers and takes account of contextual issues like markets for inputs and outputs, community and other institutions and policy environments that influence farm households. The project in Ethiopia facilitates wider scaling of validated crop-livestock-natural resource management technologies to reach and benefit more smallholder farmers. Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) is a three-year (2021–2023) project that operates in six African countries, including Ethiopia. The project is supported by a grant from the International Development Association (IDA) of the World Bank and will enhance the research and capacity-building activities of CGIAR and its partners. AICCRA in Ethiopia aims to strengthen the capacity of targeted national partners and stakeholders of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa to access and implement at scale validated climate-smart agriculture technologies, climate information services and climate-informed digital ag-advisories to build the resilience of agri-food systems. The value chains considered for AICCRA’s project in Ethiopia include beans, wheat, small ruminants and livestock feed and forage options. The AICCRA project in Ethiopia has eight research activities, four of which the livestock feed and forage options value chain contributes to. These four are capacity building to support the implementation of climate-smart agriculture (CSA) technology packages; identification of climate, gender and social inclusion-smartness of CSA packages; prioritization and awareness increase of best-bet CSA options and approaches for key value chains; and integration of climate-smart options and tailored climate-smart innovation (CSI) advisory systems for specific value chains. The Sustainable Intensification of Mixed Farming Systems (SIMFS) initiative aims to provide equitable, transformative pathways for improved livelihoods of actors in mixed farming systems through sustainable intensification within target agroecologies and socio-economic settings. Through action research and development partnerships, the initiative will improve smallholder farmers' resilience to weather-induced shocks, provide a more stable income and significant benefits in welfare, and enhance social justice and inclusion for 13 million people by 2030. Activities will be implemented in six focus countries globally, representing diverse mixed farming systems as follows: Ghana (cereal–root crop mixed), Ethiopia (highland mixed), Malawi (maize mixed), Bangladesh (rice mixed), Nepal (highland mixed), and Lao People's Democratic Republic (upland intensive mixed/ highland extensive mixed). Africa RISING, AICCRA projects and SIMFS initiative contracted a consultant to undertake media and communications-related activities. These included media assessment, facilitating media partnership, training radio journalists on livestock feed and forage technologies, and monitoring the radio broadcasts.